RESPEK DAN REKOGNISI: RESOLUSI KONFLIK WADAS: Analisis Resolusi Konflik Wadas Dalam Perspektif Teori Rekognisi Axel Honneth - Pariyatman, M. Harland; Santoso, Puguh; Madjid, Adnan (JURNAL KOMUNIKATIO, 2022)
It can be said that mining projects, dam construction, and other similar endeavors present many obstacles. Mining, dam building, and similar businesses are complicated by environmental impact assessments and land acquisition issues. This research was conducted using the literature review method. This strategy is intended to search, evaluate, and synthesize the best available evidence in scientific journal publications. The aim is to collect informative and evidence-based responses to the research topic. In Axel Honneth’s Theory of Recognition, the descriptive analysis provides a precise, objective, methodical, analytical, and critical description, and explanation of wadas conflict. We must not forget Abraham Maslow’s description of the hierarchy of human needs in psychology. Maslow described the Hierarchy of Needs hierarchically, including physiological conditions, the need for security, the need for belonging and love, and the need for self-esteem. In conflict resolution, the origins of disagreement are determined so that consensus can support community stability and integrity. The resolution of the conflict will indirectly result in recognition of Axel Honneth.